On the Interaction of Subjective Meanings - LAMBARJYAN, SRBUHI (Bulletin of Yerevan University H: Russian Philology, 2021)
The paper is devoted to the relations of persuasiveness and the other subjective categories: modality and triangle ʻI-here-nowʼ. The author describes some difficulties in realizations of the persuasive meanings in these conditions and some problems of interaction of the category of persuasiveness and the grammatical mood.